Mobilising knowledge in public health: reflections on ten years of collaborative working in Fuse, the Centre for Translational Research in Public Health. (1st November 2020) - van der Graaf, Peter; Cheetham, Mandy; Lake, Amelia; Welford, Mark; Rushmer, Rosemary; Shucksmith, Janet; Rhodes, Avril
Abstract : Background: Fuse was established in 2008 as one of five public health research centres of excellence in the UK funded by the UK Clinical Research Centres collaboration. The centre works across five universities in the North East of England. This is an innovative collaboration and enables the pooling of research expertise. A prime focus of the centre is not just the production of excellent research, but also its translation into usable evidence, a dual focus that remains uncommon.Aims/objectives: This practice paper outlines Fuse's approach to knowledge exchange (KE) by reflecting on ten years of collaborative research between academics and policy and practice partners in the North East of England. We will describe the principles and assumption underlying our approach and outline a conceptual model of four steps in Fuse's KE process to develop collaborative research and achieve meaningful impact on policy and practice.Key conclusions: Our model describes a fluid and dynamic approach to knowledge exchange broken down in four steps in the KE process that are concurrent, iterative and vary in intensity over time: awareness raising; knowledge sharing; making evidence fit for purpose; and supporting uptake and implementation of evidence. These steps support the relational context of KE. Relationship building and maintenance is essential for all stages of KE to develop trust and explore the meaning and usefulness of evidence in a multi-directional information flow that supports the co-creating and application of evidence.